Akkermansia muciniphila and its outer protein Amuc_1100 regulates tryptophan metabolism in colitis. Issue 20 (17th September 2021) - Gu, Zhenyang; Pei, Wenlong; Shen, Yonghua; Wang, Lijuan; Zhu, Jun; Zhang, Yi; Fan, Shengxian; Wu, Qian; Li, Lei; Zhang, Zhan
Abstract : A. muciniphila and its outer membrane protein Amuc_1100 restored the aberrant tryptophan metabolism in colitis. Abstract : Dietary interventions, including dietary ingredients, nutrients and probiotics, exert anti-inflammatory effects in ulcerative colitis (UC). Our previous study showed that Akkermansia muciniphila ( Akk ), a promising probiotic, could protect against colitis via the regulation of the immune response. However, whether it can restore aberrant tryptophan (Trp) metabolism during colitis remains unclear. In this study, untargeted serum metabolomics of patients with UC and colitis mice showed that Trp metabolism was activated, which was confirmed by quantification of Trp metabolites from a validation cohort and animal study. Integrative analysis of faecal metagenomes and serum metabolomes revealed significant associations between Akk and three Trp metabolites. Live Akk, pasteurised Akk and Amuc_1100 failed to restore the reduction in Trp metabolites involved in the serotonin pathway in colitis mice. However, live Akk, pasteurised Akk and Amuc_1100 increased kynurenine (Kyn) but decreased 2-picolinic acid (PIC) levels and the PIC/Kyn ratio without regulating any of the genes involved in Trp metabolism, suggesting that they could suppress the Kyn pathway (KP) independent of colon tissue. In addition, they could significantly restore the enrichment of Trp metabolism mediated by faecal microbiota. Specifically, live Akk, pasteurised Akk and Amuc_1100 could significantly offset the reduction in indoleacetic acid (IAA) levels. Pasteurised Akk significantly elevated the serum levels of indole acrylic acid (IA). In addition, live Akk, pasteurised Akk and Amuc_1100 could upregulate aryl hydrocarbon receptor (AhR) targeted genes, including CYP1A1, IL-10 and IL-22, suggesting that Akk could activate AhR signaling by regulating Trp metabolism, thereby attenuating colonic inflammation.